The Preparation of Master's‐Level Professional Counselors for Positions in College and University Counseling Centers. Issue 3 (October 2014) - Shaw, Brian M.; Remley, Theodore P.; Ward, Christine
<x xml:space="preserve">Abstract</x> This study investigated college and university counseling center directors' perceptions of the adequacy of the preparation of master's‐level counselors for work in college and university counseling centers. Results indicated that counselors were rated on average as prepared; however, many directors had concerns about counselors' ability to work with students presenting more severe mental health issues. Findings are discussed, and implications for the training and preparation of college counseling practitioners are presented.